Preferred Health Resources and Use of Social Media to Obtain Health and Depression Information by Adolescent Mothers. Issue 4 (7th August 2014) - Logsdon, M. Cynthia; Bennett, Gary; Crutzen, Rik; Martin, LuAnn; Eckert, Diane; Robertson, Ashley; Myers, John; Tomasulo, Roselyn; Gregg, Jennifer; Barone, Michael; Lynch, Tania; Flamini, Laura
<x xml:space="preserve">Abstract</x> Problem Little is known about how adolescent mothers use social media and the Internet, especially to access health information. Methods In this cross‐sectional, descriptive study, adolescent mothers were recruited from an academic medical center after the birth of their child (n = 94) or from a state‐funded, home visitation program during the first year after birth (n = 91). They completed the Pew Internet Survey: 37 questions related to use of social media and Internet, particularly in regard to obtaining health information. Findings All adolescent mothers used a computer and almost all went online. Most accessed the Internet by cell phone (67.4%) and used social media. The health topics searched most frequently were pregnancy/birth control (85.8%), sexually transmitted diseases (n = 134, 72.6%) and HIV (66.3%). Response to survey questions differed between the two groups (adolescent mothers surveyed after birth from academic medical center and adolescent mothers surveyed in the first postpartum year in the community). Conclusions Adolescent mothers spend significant time on the Internet including searching for health information. Cell phones are their preferred methods for accessing the Internet, and they use social media. Thus, social media and the Internet are potentially feasible and acceptable vehicles to deliver health interventions to adolescent mothers.